Baryonic violation of R parity from anomalous U(1)H (2013)
ABSTRACT: Supersymmetric scenarios with R-parity conservation are becoming very constrained due to the lack of missing energy signals associated to heavy neutral particles, thus motivating scenarios with R-parity violation. In view of this, we consider a supersymmetric model with R-parity violation and extended by an anomalous horizontal U(1)H symmetry. A self-consistent framework with baryon-number violation is achieved along with a proper suppression for lepton-number violating dimension-five operators, so that the proton can be sufficiently stable. With the introduction of right-handed neutrinos, both Dirac and Majorana masses can be accommodated within this model. The implications for collider physics are discussed.